Server client configuration to lock and unlock computer using barcode reader verification [electronic resource] - 377895 Zukhairi Md Yusuf; Fakulti Kejuruteraan Elektrik (2004)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Mekatronik)) - Universiti Teknologi Malaysia, 2004